2009
DOI: 10.1097/shk.0b013e31817fd1d6
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Vasopressin and Copeptin Levels in Noncardiac Surgery Patients

Abstract: Further information on the endogenous arginine vasopressin (AVP) response in patients with postoperative systemic inflammatory response syndrome (SIRS) and vasodilatory shock would provide more insight into the pathophysiology of SIRS-associated cardiovascular failure and help indicate AVP therapy. Patients after uncomplicated abdominal surgery without SIRS (n = 10), critically ill patients after noncardiac surgery with SIRS (n = 9), and patients with SIRS plus vasodilatory shock (n = 22) were included in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Numerous pathophysiological mechanisms have been postulated as contributing to cardiovascular failure in patients with severe sepsis and septic shock. Vascular tone loss and the subsequent decrease in arterial blood pressure and tissue perfusion were indicated as the result of an altered balance of endogenous vasopressor/vasodilator mediators, qualitative and quantitative downregulation of endogenous vasoconstrictor hormone receptors, and inappropriately low levels of neuroendocrine stress hormones, such as arginine vasopressin (AVP) and cortisol [5,6,12,14,21,27].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous pathophysiological mechanisms have been postulated as contributing to cardiovascular failure in patients with severe sepsis and septic shock. Vascular tone loss and the subsequent decrease in arterial blood pressure and tissue perfusion were indicated as the result of an altered balance of endogenous vasopressor/vasodilator mediators, qualitative and quantitative downregulation of endogenous vasoconstrictor hormone receptors, and inappropriately low levels of neuroendocrine stress hormones, such as arginine vasopressin (AVP) and cortisol [5,6,12,14,21,27].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported associations of copeptin levels with adverse outcomes, namely mortality [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…These studies include patients with sepsis [16,17], pneumonia and lower respiratory tract infections [16,18,19], stroke [20,21], acute myocardial infarction and congestive heart failure [22][23][24][25], as well as diabetes type 2 [26], metabolic syndrome [27] and diabetes insipidus [28]. Also in primary care, copeptin was found to predict risk in patients with heart failure [29,30], but there is no comprehensive data assessing the usefulness of serum copeptin levels as a general "risk marker" in a patient sample from primary care contacting general practitioners (GPs) due to acute respiratory tract infections (ARTIs).…”
Section: Introductionmentioning
confidence: 99%
“…The great advantage is that copeptin is very stable in plasma samples and can be measured by immunoluminometric assay, thus turning it into a useful and indicative surrogate of plasmatic AVP levels, with the additional advantage that its measurement is feasible in daily clinical practice [30,31]. Thus, the copeptin evaluation of time course could bring additional and valuable data to better understanding the role of vasopressin in the pathophysiology of surgical stress response.…”
Section: Correlations Between Plasmatic Avp and Some Selected Variablesmentioning
confidence: 99%